Meeting clinical needs for and sidestepping supply chain threats to COVID-19 testing through continuous process improvement. (28th October 2021) - Rice, F; Yip, T; Bolster LaSalle, C; Graf, E
Abstract: Introduction/Objective: The first human case of SARS-CoV-2 infection was reported in December of 2019. By late February 2020 evidence of community transmission in the United States was documented and soon it developed into a global pandemic. On March 11, 2020, the Mayo Clinic Arizona's Microbiology Laboratory introduced a PCR test for diagnosis of SARS-CoV-2 infection. Even as testing demands exponentially increased, the hospital relied on timely results to assist in directing patient care. In order to provide timely results in the face of continuously emerging supply chain threats, we needed to increase our capacity for SARS-CoV-2 PCR testing by reducing technologist time and reagent waste, without impacting turnaround time or other quality metrics such as repeat rate. Methods/Case Report: Technologist time was measured in hands-on time per specimen. Reagent use was defined by the volume of lysis buffer (the primary rate limiting reagent due to supply chain constraints) used per sample. Turnaround time was measured from receipt in lab until result verification and the rerun rate is the percent of specimens with an internal control (IC) failure, an indicator of specimen or process quality. Unnecessary steps were determined using a process map, spaghetti diagram and waste walk. Improvements included simplifying steps, changes to protocols and lab design. Impacts of the improvements were measured for 5 months post-implementation. Results (if a Case Study enter NA): Process improvements reduced technologist time per sample by 30.8 seconds and decreased critical reagent needs by 23.6%. Improvements led to 104, 000 in just reagent savings over 5 months. Turnaround time and rerun rates were not negatively impacted. Conclusion: By creating the leanest possible workflow, we were able to meet the demands for accurate and timely SARS-CoV-2 results. In future workflows, we will continue to implement lean processes and ensure the most efficient use of limited resources.